Child abdominal tumour in tropical context: Think about schistosomiasis! - A. M. Napon; E. Bandré; Z. Nikiéma; O. Diallo; I. Ouédraogo; S. Douamba Kaboret; L. C. Lougué Sorgho; A. Alfidja; L. Boyer (Wolters Kluwer Medknow Publications, 2014)
Schistosomiasis presenting as an abdominal mass with chronic pain in a child is not common. This report presents case of child presenting with schistosomiasis presenting as an abdominal mass with chronic pain. Abdominal ultrasonography did not particularly contribute to definitive pre-operative diagnosis. However, pathological examination of surgical specimen confirmed Schistosoma mansoni eggs in the biospy. A decrease in the mass volume was noticed under medical treatment (Biltricide). The aim of this report was to intimate clinicians on possible abdominal schistosomiasis as differential diagnosis of childhood abdominal mass. This is a clarion call for a high index of suspicion of childhood abdominal schistosomiasis in children presenting with abdominal mass in a tropical setting.